Early nutrition transition in Haiti: linking food purchasing and availability to overweight status in school-aged children. Issue 18 (4th July 2016) - Morshed, Alexandra B; Becker, Haley V; Delnatus, Jacques Raymond; Wolff, Patricia B; Iannotti, Lora L
Abstract: Objective: The primary aim was to examine the association of socio-economic factors and diet with overweight (including obesity) among school-aged children in Haiti. The secondary aim was to describe food availability and the physical activity built environment in participating schools. Design: This cross-sectional study examined baseline data from the intervention Mamba study assessing the effectiveness of a fortified peanut butter paste in school-aged children. Logistic regression modelling was used to test hypothesized factors in association with overweight status. Setting: Six primary schools in Cap-Haitien, the second largest city in Haiti. Subjects: Children ( n 968) aged 3–13 years, in good health and enrolled in a participating school for the 2012/13 school year. Results: Child age (adjusted OR (AOR); 95 % CI=0·25; 0·12, 0·56), child age squared (1·08; 1·03, 1·13), always purchasing food at school (3·52; 1·12, 11·08), mother's BMI (1·10; 1·04, 1·16) and household ownership of a bicycle (0·28; 0·11, 0·71) were significantly associated with overweight (likelihood ratio=36, P <0·0001). Consumption of fish was significantly lower in overweight children in the binary analysis ( P =0·033) and improved the fit of the model. Schools had limited time and space for physical activity and foods sold by vendors were predominantly high in sugar or fat. Conclusions: To our knowledge the present study is the first to examine the covariates of childhood overweight or describe school food availability and physical activity built environments in Haiti. Further research is necessary to identify intervention targets and feasible, cost-effective approaches for prevention of obesity in Haiti children.